Riflessioni sul curricolo a partire da Dewey. Qualche nota educativa - Finazzi, Fausto (Studi sulla Formazione/Open Journal of Education, 2017)
In his pedagogical reflections, Dewey paid considerable attention to the curricu-lum as a means for the schools to accomplish progressive education. On several occasions he dealt with this subject in his writings, especially to compare tradi-tional education to the educational model, with all its features, which he upheld. His directions have not always been correctly grasped for various reasons. This paper intends to clarify his message on these issues, first of all presenting some of the principles about school maintained by him, secondly focusing on the prob-lems that a curriculum involves in his opinion and eventually putting forward a possible interpretative solution of some implicit meanings of Dewey’s message.